Are behavioral interventions a better choice for atopic dermatitis patients? A meta-analysis of 6 randomized controlled trials - Wenying Zhong; Wei Li; Guangsheng Wu (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background The treatment for atopic dermatitis (AD) has been the focus of clinical research, and behavioral intervention is considered an indispensable treatment method. To our knowledge, no relevant meta-analysis has evaluated the effects of behavioral interventions on atopic dermatitis. Objectives To evaluate the effects of behavioral interventions on atopic dermatitis. Methods The authors searched PubMed, EMBASE, and Cochrane CENTRAL to retrieve relevant RCTs (up to Feb 2022). The search strategy involved a combination of related keywords. The Cochrane Q and I2 statistics were used to assess heterogeneity. Results Six RCTs involving seven reports with 246 patients were included. The results suggested that behavioral interventions could relieve eczema severity (correlation coefficient [r = −0.39]; p < 0.001) and scratching severity significantly (r = −0.19; p = 0.017), while not affect itching intensity (r = −0.02; p = 0.840). A sensitivity analysis confirmed the robustness of the results. Study limitations An important limitation of this study was the insufficient number of RCTs and the limited sample size. In addition, the study lacked a control group receiving a type of intervention other than the experimental protocol. Another limitation was the short duration of follow-up. Conclusions This study suggests that behavioral interventions could be effective in treating atopic dermatitis by reducing eczema and scratching severity. Additionally, habit-reversal behavioral therapy may be more effective for treating atopic dermatitis.